BONGGOL JAGUNG DAN KULIT PISANG RAJA (Musa Paradisiaca) EFEKTIF SEBAGAI ADSORBEN Fe DALAM AIR SUMUR - Fitria Shella Widyayuningsih; Pratiwi Hermiyanti; Darjati (Gema Lingkungan Kesehatan, 2022)
Well water in Kedung Sekar village which contains high levels of iron (Fe) can cause economic losses such as clogged pipes, yellow clothes and skin irritation. Utilization of waste corn cobs and Musa Paradisiaca peels as activated carbon can reduce Fe levels in water. The purpose of this study was to compare the effectiveness of activated carbon made from corn cobs and Musa Paradisiaca peels to reduce Fe content in water. This type of research is pre-experimental. Examination of Fe levels in the laboratory to determine the content before and after treatment. Treatment using a variety of doses of activated carbon 4 g, 6 g, 8 g. Data analysis used a statistical test, namely One Way Anova and compared it with the Minister of Health Regulation Number 32 of 2017 concerning Environmental Quality Standards and Water Health Requirements for Sanitary Hygiene Needs. The results showed that there was a decrease in Fe levels at a dose of 8 g for corn cobs activated carbon by an average of 0.95 mg/l or 94.36% and for Musa Paradisiaca peels activated carbon there was a decrease at a dose of 8 g of 1.56 mg/l or 90.74%. Statistical testing obtained the value of Sig. 0.000, which means that there is a difference in the decrease in iron (Fe) levels after adsorption with activated carbon from corn cobs and Musa Paradisiaca peels. The conclusion that can be formulated is that activated carbon from corn cobs and Musa Paradisiaca peels can reduce iron (Fe) levels in water. Suggestions for other researchers can use variations of activator KOH, CaCl2, NaOH to make activated carbon and check the quality of charcoal according to SNI 06-3730-1995.